PortFIR®: Multi Format Availability of Portuguese Food Composition DataBase - Fernandes, Paulo (2018)
Introduction: The Portuguese Food Composition DataBase (PFCDB) is the reference table of food composition in Portugal. Created in 1961, it has been available on printed support since then. Since 2007 the demand for digital supported information originated a CD-Rom (book in PDF and Excel file with complete data). In 2010 an online tool was created on INSA website, beyond the PDF and CD.